Well Water Site Selection at Local Scale Using Geographical Information System for Flood Victim in Malaysia - Koh Liew See; Nayan Nasir; Saleh Yazid; Hashim Mohmadisa; Mahat Hanifah; A. Rahaman Zullyadini (Indonesian Journal of Geography, 2018)
Clean water supply is a major problem among flood victims during flood events. This article aims to determine the sites of well water sources that can be utilised during floods in the District of Kuala Krai, Kelantan. Field methods and Geographic Information Systems (GIS) were applied in the process of selecting flood victim evacuation centres and wells. The data used were spatial data obtained primarily, namely the well data, evacuation centre data and flood area data. The well and evacuation centre data were obtained by field methods conducted to determine the position of wells using global positioning system tools, and the same for the location of the evacuation centres. Information related to evacuation centres was obtained secondarily from multiple agencies and gathered into GIS as an evacuation centre attribute. The flood area data was also obtained via secondary data and was digitised using the ArcGIS software. The data processing was divided into two stages, namely the first stage of determining the flood victim evacuation centres to be used in this research in a structural manner based on two main criteria which were the extent to which an evacuation centre was affected by the flood and the highest capacity of victims for each district with the greatest impact to the flood affected population. The second stage was to determine the location of wells based on three criteria, namely i) not affected by flood, ii) the closest distance to the selected flood victim evacuation centre and iii) located at different locations. Among the main GIS analyses used were locational analysis, overlay analysis, and proximity analysis. The results showed that four (4) flood evacuation centres had been chosen and matched the criteria set, namely SMK Sultan Yahya Petra 2, SMK Manek Urai Lama, SMK Laloh and SK Kuala Gris. While six (6) wells had been selected as water sources that could be consumed by the flood victims at 4 evacuation centres in helping to provide clean water supply, namely Kg. Keroh 16 (T1), Kg. Batu Mengkebang 10 (T2), Lepan Meranti (T3), Kg. Budi (T4), Kg. Jelawang Tengah 2 (T5) and Kg. Durian Hijau 1 (T6). With the presence of the well water sources that can be used during flood events, clean water supply can be distributed to flood victims at the evacuation centres. Indirectly, this research can reduce the impact of floods in the future, especially in terms of clean water supply even during the hit of a major flood.